GIRLS, GADGETS AND GATEKEEPERS: HOW GENDER AND CLASS ASPIRATIONS SHAPE ADOLESCENT ACCESS TO MOBILE PHONES IN MUMBAI, INDIA - Bhallamudi, Isha (AoIR Selected Papers of Internet Research, 2021)
Within a patriarchal, caste-based and restrictive family setup, how do gender and class work together to shape adolescent girls’ access to mobile phones in Mumbai, India? How do adolescent girls mediate their own independent aspirations and desires to variously fit within or subvert these frameworks of class stability and social morality? This paper addresses these question by using a mixed-methods study of 59 group interviews and 278 surveys with adolescents aged 13-15 in Mumbai. Taking an intersectional analytical framework, the findings show how gender and class together, create varying standards of respectable femininity and class distinction that families aspire to and cultivate in adolescent girls. The mobile phone can be seen as both a threat and a necessity to the maintenance of these standards of respectability, resulting in families variously enabling or constraining access to mobile phones by girls. Rather than interpreting the findings through binaries of lower-class/upper-class or empowered/constrained, I instead consider how classed ideals of respectable femininity create different aspirational conditions for girls belonging to each class group, and form the cultural frames of everyday life. I explore what implications this might have for adolescents girls’ understandings and enactments of independence, and how they use the site of the mobile phone to make these enactments.